β-D-Galactose-Functionalized Pillar[5]arene With Interesting Planar-Chirality for Constructing Chiral Nanoparticles - Sun, Guangping; Pu, Liangtao; Pangannaya, Srikala; Xiao, Tangxin; Hu, Xiao-Yu; Jiang, Juli; Wang, Leyong (Frontiers in Chemistry, 2019)
Planar-chiral pillar[5]arenes bearing β-D-galactose substituents on both rims have been successfully synthesized and effectively separated by silica gel chromatography with a high yield. The obtained (Sp)- and (Rp)-β-D-galactose functionalized pillar[5]arenes [(Sp-D)-GP5 and (Rp-D)-GP5] exhibit the Sp and Rp planar chirality. Furthermore, (Sp-D)-GP5 and (Rp-D)-GP5 can not racemize according to dynamic 1H NMR and CD spectra. Notably, GP5 is able to capture a guest molecule (DNS-CPT) to form a host-guest supramolecular amphiphile, which can further self-assemble into chiral nanoparticles with the Sp and Rp planar chirality of (Sp-D)-GP5 and (Rp-D)-GP5 still being retained, suggesting GP5 could be as reliable chiral sources to transfer the Sp and Rp planar chirality.